2022
DOI: 10.3390/foods11131855
|View full text |Cite
|
Sign up to set email alerts
|

Easy-to-Use Visual Sensing System for Milk Freshness, Sensitized with Acidity-Responsive N-Doped Carbon Quantum Dots

Abstract: This study established a flexible and eye-readable sensing system for the easy-to-use, visual detection of milk freshness, using acidity-responsive N-doped carbon quantum dots (N-CQDs). N-CQDs, rich in amino groups and with characteristic acidity sensitivity, exhibited high relative quantum yields of 25.2% and an optimal emission wavelength of 567 nm. The N-CQDs fluorescence quenching upon the dissociated hydrogen ions (H+) in milk and their reacting with the amino groups produced an excellent linear relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Additionally, when one evaluates the quality of milk in relation to freshness, an important indicator is the presence of lactic acid. 15 The production of acidifying metabolites in milk is primarily caused by the activity of mesophilic bacteria, which grow well at ambient temperatures. 16 Prompt and effective cooling of milk after milking can significantly reduce the growth of mesophilic bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when one evaluates the quality of milk in relation to freshness, an important indicator is the presence of lactic acid. 15 The production of acidifying metabolites in milk is primarily caused by the activity of mesophilic bacteria, which grow well at ambient temperatures. 16 Prompt and effective cooling of milk after milking can significantly reduce the growth of mesophilic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have shown that exposure to H 2 O 2 in both short- and long-term can lead to cellular damage and is associated with several diseases, including diabetes, cancer, and cardiovascular and degenerative diseases. Therefore, it is crucial to develop analytical methods that are both simple and affordable while also providing rapid detection of H 2 O 2 . Additionally, when one evaluates the quality of milk in relation to freshness, an important indicator is the presence of lactic acid . The production of acidifying metabolites in milk is primarily caused by the activity of mesophilic bacteria, which grow well at ambient temperatures .…”
Section: Introductionmentioning
confidence: 99%